Parodie horacjańskie. Przekład siedmiu pieśni Macieja Kazimierza Sarbiewskiego - Ryczek, Wojciech (Symbolae Philologorum Posnaniensium Graecae et Latinae, 2019)
The paper proposes the translations into Polish of the following Latin odes composed by Mathias Casimir Sarbiewski: I 19 Urit me patriae decor, II 14 Diva, ventorum pelagique praeses, II 18 Reginam tenerae dicite virgines, I 26 Aurei regina, Maria, caeli, III 2 Cum tu, Magdala, lividam, IV 7 Iessea quisquis reddere carmina, IV 31 Vides, ut altum fluminis otium. All of the texts included in this collection are strongly related to imitating of Horatian lyrical discourse (parodia Horatiana). A short introduction and the most significant references to Horace’s odes and notes have been provided.